Poder y crisis en América Latina - Quijano Obregón, Aníbal (2022)
We publish a text by Aníbal Quijano that aims to open up some questions related to the relations between society and the State in Latin America. The exploration of this problem has as its starting point the discussion of the question of “participation” in its two modalities: on the one hand, “self-management participation”, as the intervention of workers in the management of companies; and, on the other hand, the “participation” of the “social movements”, where their relations with the State are closely examined. The examination of these problems explores them from the perspective of the problematic of power. He argues that the power structure in Latin America is in crisis to the extent that capitalist “modernization” exploded “long before it was able to produce that capitalist homogenization of Latin American society.” One of its consequences is the disorganization of social grouping patterns, both class and non-class, and the emergence of a new structural heterogeneity and the multi-social and cultural insertion of broad sectors of the population. In this situation, Quijano writes, “what is called ‘social movements’, with their peculiar characteristics, expresses the reality of power in Latin America, that is, its time of crisis.” The essay concludes by outlining the perspectives that are open to the relations between society and the State in Latin America.